أثر مستوى التحصيل السابق والتعليم باستخدام نموذج رايجلوث (Reigiluth) في تحصيل بعض مفاهيم مادة الدراسات الاجتماعية (دراسة تجريبية على عينة من تلامذة الصف الرابع الأساسي في محافظة اللاذقية) - إبراهيم, هاشم; شيبان, نورا (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدف البحث إلى اختبار أثر استخدام نموذج رايجلوث ( Reigiluth)، وكذلك أثر مستوى التحصيل السابق، والتفاعل بين نمط التعليم ومستوى التحصيل السابق في تحصيل تلامذة الصف الرابع الأساسي لبعض مفاهيم مادة الدراسات الاجتماعية في محافظة اللاذقية. وقد صممت الباحثة برنامجاً تعليمياً - تعلمياً وفق نموذج (رايجلوث)، واختباراً تحصيلياً تم تطبيقهما على عينة من تلامذة الصف الرابع الأساسي في مدرسة الحسين بن علي الثانية. وبلغ عدد أفراد العينة (70) تلميذاً وتلميذةً موزعين على مجموعتين تجريبية وضابطة. وتوصل البحث إلى النتائج التالية: وجود فرق ذي دلالة إحصائية عند مستوى دلالة (0.05) بين متوسطي درجات تلامذة المجموعتين التجريبية والضابطة في الاختبار التحصيلي البعدي يعزى إلى نمط التعليم المستخدم (نموذج رايجلوث – الطرائق المتبعة في مدارس التعليم الأساسي) إذ تفوقت المجموعة التجريبية التي تعلمت باستخدام نموذج رايجلوث على المجموعة الضابطة التي تعلمت بالطرائق المتبعة في مدارس التعليم الأساسي، كما تبين وجود فرق ذي دلالة إحصائية عند مستوى دلالة (0.05) بين متوسطي درجات تلامذة المجموعتين التجريبية والضابطة في الاختبار التحصيلي البعدي يعزى إلى مستوى التحصيل السابق (مرتفع – متوسط – منخفض) إذ تفوق التلامذة مرتفعو التحصيل على متوسطي التحصيل ومنخفضيه، كما تفوق التلامذة متوسطو التحصيل على منخفضي التحصيل، وجود فرق ذي دلالة إحصائية عند مستوى دلالة (0.05) بين متوسطي درجات تلامذة المجموعتين التجريبية والضابطة في الاختبار التحصيلي البعدي يعزى إلى التفاعل بين نمط التعليم المستخدم (نموذج رايجلوث – الطرائق المتبعة في مدارس التعليم الأساسي) ومستوى التحصيل السابق (مرتفع – متوسط – منخفض) إذ تفوق تلامذة المجموعة التجريبية (مرتفعو التحصيل – متوسطو التحصيل – منخفضو التحصيل) على ذويهم في المجموعة الضابطة. وقد قدم البحث الحالي عدداً من التوصيات. This study aims at testing the effect of using Reigiluth’s Model, the effect of previous achievement level, and the interaction between the teaching Model and the previous achieving level on learning some concepts of a social studies course designed for basic education Fourth-Graders in Lattakia. The researcher designs a teaching-learning program according to Reigiluth’s Model and achievement test, applying it to a sample of basic education Fourth-Graders in (Hussein bin Ali 2). The sample consists of (70) male and female students are divided into two groups (experimental and control). This study has obtained the following results: There are statistically significant differences at the index level (0.05) between average experimental group scores and those of the control group in the post-test attributed to the teaching Model (Reigiluth’s Model –Methods used in basic teaching schools), where the students of the experimental group taught by using Regolith’s Model have excelled those in the control group taught by using Methods used in basic teaching schools. There are also statistically significant differences at the index level (0.05) between average experimental group scores and those of the control group in the post-test attributed to the previous achievement Level (high, medium, low) where high achievement students have excelled medium and low achievement ones; medium achievement students have also excelled low achievement ones. Moreover, there are statistically significant differences at the index level (0.05) between average experimental group scores and those of the control group in the post-test attributed to the interaction between the teaching Model (Reigiluth’s Model–Methods used in basic teaching schools) and the previous achievement level (high, medium, low), where the students of the experimental group (high, medium, and low achievement ) have excelled their peers in the control group. This study has offered some recommendations.